Analysis of The Role of Bhabinkamtibmas To Maintain Security and Order In Sumbersari Village Sleman - Isnawan, Fuadi (Universitas Muhammadiyah Surabaya, 2024)
Ensuring security and order requires both police efforts and community participation. In Tiwir Village, Sumbersari, Moyudan, Sleman, a person with a mental illness caused disturbances by stealing items and entering homes. The purpose of this study is to analyze the role of Bhabinkamtibmas in Sumbersari Village in maintaining community security and order amidst disturbances caused by individuals with mental disorders (ODGJ). The study focuses on identifying the efforts made by Bhabinkamtibmas to address these disturbances and the factors that hinder their effectiveness. The method used in this research is the empirical juridical method.The approach used in this research is a legal sociology approach. The result is Bhabinkamtibmas as the frontline of village policing, they ensure a constant presence, conduct monitoring, and engage persuasively with the community.. However, challenges arise from a lack of legal awareness among families of individuals with mental illness. This gap in legal knowledge impedes their ability to manage disruptive behaviors and exacerbates community tolerance of such disturbances. The resulting reluctance to address these issues effectively hinders Bhabinkamtibmas efforts in maintaining security and fostering community cooperation.